-2(c-d)+(c-3d)-5(c-d)=

Simple and best practice solution for -2(c-d)+(c-3d)-5(c-d)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(c-d)+(c-3d)-5(c-d)= equation:


Simplifying
-2(c + -1d) + (c + -3d) + -5(c + -1d) = 0
(c * -2 + -1d * -2) + (c + -3d) + -5(c + -1d) = 0
(-2c + 2d) + (c + -3d) + -5(c + -1d) = 0

Remove parenthesis around (c + -3d)
-2c + 2d + c + -3d + -5(c + -1d) = 0
-2c + 2d + c + -3d + (c * -5 + -1d * -5) = 0
-2c + 2d + c + -3d + (-5c + 5d) = 0

Reorder the terms:
-2c + c + -5c + 2d + -3d + 5d = 0

Combine like terms: -2c + c = -1c
-1c + -5c + 2d + -3d + 5d = 0

Combine like terms: -1c + -5c = -6c
-6c + 2d + -3d + 5d = 0

Combine like terms: 2d + -3d = -1d
-6c + -1d + 5d = 0

Combine like terms: -1d + 5d = 4d
-6c + 4d = 0

Solving
-6c + 4d = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-4d' to each side of the equation.
-6c + 4d + -4d = 0 + -4d

Combine like terms: 4d + -4d = 0
-6c + 0 = 0 + -4d
-6c = 0 + -4d
Remove the zero:
-6c = -4d

Divide each side by '-6'.
c = 0.6666666667d

Simplifying
c = 0.6666666667d

See similar equations:

| -0.5x^2+2x-70=0 | | 6a+4=a+7 | | -20x^2-8x+64=0 | | 2n^2+33n-17=0 | | 2.5x+0.25x=0.75+x | | 4x+9=3x+5 | | 6m^2=23m-15 | | 0.36(18)+0.04x=0.12(6+x) | | -2x+3y-5x-(-8y)+9y= | | 4+2x*6=x*-10+2 | | 9x^2=33x-30 | | 8x=3x-45 | | 4m^2-12m+9=0 | | -7-3y=8 | | 201-2x=43+16 | | 8x-51=3x | | 5-4y+x+9y= | | 4x+13=-7-9x | | 155-6x=4x | | 4(x+5y)+(5x+y)= | | 1.23x+0.125x=0.375+x | | x+8=6-3x | | 2x^2+50=20x | | 9t+3(1-4t)= | | -37.5x^2=-37.5 | | -(a+3)=-(a+1)-2 | | 5x+30=90 | | 0.36(24)+0.06x=0.18(18+x) | | 3t+3(1-3t)= | | 5t+4(1-2t)= | | 9+2x*5=x*6+13 | | 2048x^3y=0 |

Equations solver categories